Umbrella review of mesenchymal stem cell-derived extracellular vesicles in preclinical models: therapeutic efficacy across diverse conditions - Mussin, Nadiar M.; Zhilisbayeva, Kulyash R.; Baspakova, Akmaral; Kurmanalina, Madina A.; Tamadon, Amin (Frontiers in Cell and Developmental Biology, 2025)
BackgroundMesenchymal stem cell-derived extracellular vesicles (MSC-EVs) have emerged as a promising cell-free therapeutic strategy for various diseases due to their anti-inflammatory, anti-apoptotic, and regenerative properties. Numerous meta-analyses have evaluated MSC-EV efficacy in preclinical animal models, but a comprehensive synthesis across diverse conditions is lacking.ObjectiveThis umbrella review aims to systematically evaluate the therapeutic efficacy, mechanisms, and methodological quality of MSC-EVs in preclinical models across multiple diseases.MethodsA systematic search of Scopus and Web of Science was conducted to identify meta-analyses published up to July 2025, focusing on MSC-EV interventions in preclinical animal models. Data were extracted on study characteristics, exosome sources, animal models, outcomes, and risk of bias. The AMSTAR 2 tool assessed meta-analysis quality, while SYRCLE and CAMARADES tools evaluated primary study bias. Narrative and quantitative syntheses summarized efficacy, heterogeneity, and publication bias.ResultsForty-seven meta-analyses covering 27 diseases were included, spanning neurological, renal, wound healing, liver, musculoskeletal, respiratory, and reproductive disorders. MSC-EVs demonstrated high efficacy, significantly improving functional scores, reducing inflammation, and promoting regeneration. Bone marrow-, adipose-, and umbilical cord-derived EVs were most effective, with modified EVs showing enhanced outcomes. Methodological quality was moderate (AMSTAR 2), with high heterogeneity (I2 > 70%) and frequent risk of bias due to poor randomization and blinding. Publication bias was noted but often robust after adjustments.ConclusionMSC-EVs exhibit robust therapeutic potential across diverse preclinical models, supporting their development as a versatile regenerative therapy. Standardization of EV protocols, improved study quality, and mechanistic insights are critical for clinical translation. This review provides a comprehensive framework for advancing MSC-EV research and application.